Castlesteads ring-grooves site (Scottish Historical and Archaeological Internet Reports, 2010)
This chapter presents a detailed archaeological description of two ring-groove structures and a group of intercutting pits. Associated artefacts include a small assemblage of lithics, one sherd of prehistoric pottery and a whetstone. This type of structure is though to have a long life span commencing in the first quarter of the second millennium BC.